2021
DOI: 10.1007/s00417-021-05203-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of uncomplicated Descemet membrane endothelial keratoplasty on the central retinal thickness

Abstract: Purpose To determine retinal thickness (RT) changes and the incidence of macular edema after uncomplicated Descemet membrane endothelial keratoplasty (DMEK-ME) in patients without ME risk factors. Methods In this retrospective study, 107 pseudophakic eyes of 74 patients with Fuchs endothelial dystrophy (FED) (79.4%) or bullous keratopathy (BK) (20.6%) underwent DMEK surgery between 2016 and 2019 at the Department of Ophthalmology, RWTH Aachen University. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(166 reference statements)
2
4
0
Order By: Relevance
“…In our study, we have found that 60% of eyes had subretinal fluid in addition to intraretinal fluid cysts, higher compared with the reported incidence in previous studies 19,20 ; we have observed no cases of isolated SRF, in agreement with the study by Flanary et al 5 . The pathophysiologic mechanisms underlying postoperative CMO after EK is similar to that of pseudophakic CMO, with the additional release of inflammatory mediators due to iris manipulation by iridectomy and intracameral gas tamponade; one study found that iris damage before and after DMEK increased the risk of post-DMEK CMO 9 , and preoperative LASER iridotomy may be associated with a lower risk of post-EK CMO 21 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, we have found that 60% of eyes had subretinal fluid in addition to intraretinal fluid cysts, higher compared with the reported incidence in previous studies 19,20 ; we have observed no cases of isolated SRF, in agreement with the study by Flanary et al 5 . The pathophysiologic mechanisms underlying postoperative CMO after EK is similar to that of pseudophakic CMO, with the additional release of inflammatory mediators due to iris manipulation by iridectomy and intracameral gas tamponade; one study found that iris damage before and after DMEK increased the risk of post-DMEK CMO 9 , and preoperative LASER iridotomy may be associated with a lower risk of post-EK CMO 21 .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, three eyes had history of DMEK in the fellow eye, however we do not believe that DMEK in the fellow eye was a contributing factor for vs-CMO after DMEK in the second eye 4,8 . Two eyes needed rebubbling after DMEK; while it is conceivable that rebubbling may increase the risk of post-EK CMO due to repeated manipulation and resulting in increased release of prostaglandins and other inflammatory mediators 9,20,26 , this association has been disputed by other studies 3,4,6,8,19 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to our study, focus was set on a larger area of the macula concerning CRT, but authors suggested that the central 1-mm zone was most sufficient due to the lack of significant differences between the 2 groups in the 3-and 6-mm subfield. 16 In summary, our study shows that even in the known or suspected presence of macular comorbidities, DMEK and triple DMEK substantially improve BCVA. However, when deciding to list a patient with macular pathologies for corneal transplantation, the potential visual limitations should be carefully discussed with the patient to set realistic expectations because the BCVA outcome was significantly worse in this subgroup.…”
Section: Discussionmentioning
confidence: 52%
“…In contrast to our study, focus was set on a larger area of the macula concerning CRT, but authors suggested that the central 1-mm zone was most sufficient due to the lack of significant differences between the 2 groups in the 3- and 6-mm subfield. 16…”
Section: Discussionmentioning
confidence: 99%